Edmund Bojanowski (1814-1871) – szkic biograficzny - Gołdyn, Piotr (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Edmund Bojanowski (1814-1871) – a landlord, writer and activist. Being grown up in patriotic and religious environment he started his studies in Wrocław and then, in Berlin but he had to stopped it due to health problems. After his return to family region he took up writing and activism. As a result of his actions, there appeared a village orphanage on May 3, 1850 in Podrzecze. This date also marks the beginning of The Congregation of the Servant Sisters of Virgin Mary Immaculate Conception, a convent created by Bojanowski. He died in 1871 and in 1999 John Paul II announced his beatification.